Religion, literature and identity in South Africa: the case of Alan Paton - Levey, D. (Koers, 2007)
This article draws on recent research into the early unpublished work of Alan Paton to suggest that the interrelationship of (English-language) literature and religion in South Africa is a much under-researched field despite numerous examples of such research elsewhere. One short case study based on Paton’s lecture on “God in modern thought” (1934) is offered. The value of a hermeneutic approach to literature that considers human identity in terms of incarnation, for example, is briefly argued and other possibilities suggested.